Ultrasound-guided erector spinae plane block for postoperative analgesia in laparoscopic liver resection: A prospective, randomised controlled, patient and observer-blinded study. (August 2021) - Kim, Doyeon; Kim, Jong Man; Choi, Gyu-Seong; Heo, Gunyoung; Kim, Gaab Soo; Jeong, Ji Seon
Abstract : BACKGROUND: Erector spinae plane block (ESPB) has been reported to manage postoperative pain effectively after various types of surgery. However, there has been a lack of study on the effect of ESPB after liver resection. OBJECTIVES: To investigate the analgesic effects of ESPB on pain control after laparoscopic liver resection compared with conventional pain management. DESIGN: Prospective, randomised controlled study. SETTING: A single tertiary care centre from February 2019 to February 2020. PATIENTS: A total of 70 patients scheduled to undergo laparoscopic liver resection. INTERVENTIONS: In the control group ( n  = 35), no procedure was performed. In the ESPB group ( n  = 35), ESPB was performed after induction of general anaesthesia. A total of 40 ml of ropivacaine 0.5% was injected at the T9 level bilaterally. After surgery, intravenous fentanyl patient-controlled analgesia was initiated. Fentanyl and hydromorphone were administered as rescue analgesics. MAIN OUTCOME MEASURES: The primary outcome was the cumulative postoperative opioid consumption at 24 h (morphine equivalent). The secondary outcomes were rescue opioid (fentanyl) dose in the postanaesthesia care unit (PACU) and pain severity at 1, 6, 12, 24, 48 and 72 h, assessed using a numerical rating scale (NRS) score. RESULTS: The median [IQR] postoperative opioid consumption during 24 hours following surgery was 48.2 [17.1] mg in the control group and 45.5 [35.8] mg in the ESPB group (median difference, 4.2 mg; 95% CI, −4.2 to 13.3 mg; P  = 0.259). Conversely, rescue opioid in PACU was 5.3 [5.0] mg in the control group and 3.0 [1.5] mg in the ESPB group (median difference, 2.5 mg; 95% CI, 1.0 to 5.0 mg; P  < 0.001). There was no significant difference in NRS scores point between the groups at any time. CONCLUSION: ESPB does not provide analgesic effect within 24 h after laparoscopic liver resection. TRIAL REGISTRATION: Clinical Trial Registry of Korea (https://cris.nih.go.kr .), identifier: KCT0003549)